Regional measures of human capital in the European Union - Christian Dreger; Georg Erber; Daniela Glocker (European Regional Science Association (ERSA), 2010)
The accumulation of the human capital stock plays a key role to explain the economic performance across regions. However, empirical evidence for this claim has been not very convincing, probably due to low quality of the data. This paper provides a robustness analysis of alternative human capital measures available for EU regions. Examining the spatial dimension can offer new insights. Most strikingly, the amount of information is tremendously enlarged. Studies based on country level data are based on heterogeneous economies to obtain a high number of observations. The heterogeneity is not fully captured by fixed effects. As the EU or at least the old and the new member states are more homogeneous geographical areas, the quality of the results should be enhanced. In addition to univariate measures of human capital, composite indicators are discussed. To examine the robustness of the results, different aggregation methods are considered. The reliability of alternative indicators is explored by the Krueger and Lindahl (2001) approach. Indicators based on wage regressions are also presented, see Mulligan and Sala-i-Martin (1997) and Gershuny and Kun (2002). Due to data availability, the latter analysis is carried out for only for German regions. The analysis shows a significant impact of construction techniques on the quality of indicators. While composite indicators and labour income measures point to the same direction, their correlation is not very high. Moreover, popular indicators should be applied with caution. Schooling and human ressources in science and technology can only explain some part, but not the bulk of the experience.
Keywords: I20; O30; O40; O52; 330; Human capital indicators; regional economic growth